2001
DOI: 10.1109/42.938237
|View full text |Cite
|
Sign up to set email alerts
|

Automated segmentation of multiple sclerosis lesions by model outlier detection

Abstract: This paper presents a fully automated algorithm for segmentation of multiple sclerosis (MS) lesions from multispectral magnetic resonance (MR) images. The method performs intensity-based tissue classification using a stochastic model for normal brain images and simultaneously detects MS lesions as outliers that are not well explained by the model. It corrects for MR field inhomogeneities, estimates tissue-specific intensity models from the data itself, and incorporates contextual information in the classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
399
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(402 citation statements)
references
References 35 publications
3
399
0
Order By: Relevance
“…These metrics were originally applied by Leemput et al 11 , Zijdenbos et al 20 , and Anbeek et al 1 to measure the concordance of their results with manual segmentation of white matter lesions. With their segmentation techniques, Leemput et al 11 and Zijdenbos et al 20 , achieved similarity indices of 0.51 and 0.68 respectively, while Anbeek et al 1 , achieved a value of 0.7 for SI for all of their study patients. In our present approach this value is 0.78 suggesting the superior performance of our method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These metrics were originally applied by Leemput et al 11 , Zijdenbos et al 20 , and Anbeek et al 1 to measure the concordance of their results with manual segmentation of white matter lesions. With their segmentation techniques, Leemput et al 11 and Zijdenbos et al 20 , achieved similarity indices of 0.51 and 0.68 respectively, while Anbeek et al 1 , achieved a value of 0.7 for SI for all of their study patients. In our present approach this value is 0.78 suggesting the superior performance of our method.…”
Section: Discussionmentioning
confidence: 99%
“…While this appears to be true for gray matter (GM) and white matter (WM) classes which follow Gaussian distribution, lesions and CSF do not follow any known distribution. For example, Van Leemput et al 11 have identified MS lesions as outliers that are not well handled by this model. In contrast, nonparametric methods such as Parzen window classifier 6 do not assume any distribution for tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Van Leemput et al (13,14) extended the concept and developed automatic segmentation of MR images of normal brains by statistical classification, using an atlas prior for initialization and also for geometric constraints. A most recent extension detects brain lesions as outliers (15) and was successfully applied for detection of multiple sclerosis lesions. Brain tumors, however, can't be simply modeled as intensity outliers due to overlapping intensities with normal tissue and/or significant size.…”
Section: Introductionmentioning
confidence: 99%
“…Boudraa et al [57] employed the FCM algorithm to 1.5 T twodimensional (2-D) MRI images for classifying normal and abnormal brain structures. Leemput et al [58] designed an automated method by using an intensity-based tissue classification and a stochastic model for detection of MS lesions from 3-D images. Zijdenbos et al [59] developed a CAD framework for the pipeline analysis of MS lesions in MRI data.…”
Section: Multiple Sclerosis Diagnosismentioning
confidence: 99%